Correction: Tuning the Schottky contacts in the phosphorene and graphene heterostructure by applying strain. Issue 33 (4th August 2016) - Liu, Biao; Wu, Li-Juan; Zhao, Yu-Qing; Wang, Lin-Zhi; Cai, Meng-Qiu
Abstract : Correction for 'Tuning the Schottky contacts in the phosphorene and graphene heterostructure by applying strain' by Biao Liu et al., Phys. Chem. Chem. Phys., 2016, 18, 19918–19925.